2006
DOI: 10.1111/j.1540-8175.2006.00301.x
|View full text |Cite
|
Sign up to set email alerts
|

Left and Right Ventricular Function Is Impaired in Behçet's Disease

Abstract: We demonstrated that myocardial velocities, were affected in patients with BD. Therefore, we conclude that right and left ventricular function is impaired in patients with BD.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
10
0
1

Year Published

2007
2007
2022
2022

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 21 publications
(12 citation statements)
references
References 17 publications
1
10
0
1
Order By: Relevance
“…Impaired LVDF in patients with BD was also documented using the lateral mitral annular velocities. 14 In agreement with our findings, Tunc et al 8 detected normal LVDF with no significant difference in diastolic parameters between patients and controls using the TDI and transmitral velocities. Similar findings were also documented in two previous studies.…”
Section: Discussionsupporting
confidence: 81%
See 1 more Smart Citation
“…Impaired LVDF in patients with BD was also documented using the lateral mitral annular velocities. 14 In agreement with our findings, Tunc et al 8 detected normal LVDF with no significant difference in diastolic parameters between patients and controls using the TDI and transmitral velocities. Similar findings were also documented in two previous studies.…”
Section: Discussionsupporting
confidence: 81%
“…6,7 While some studies suggested that BD does not result in impaired left ventricular diastolic function (LVDF), [8][9][10] others have documented impaired LVDF. [11][12][13][14] One study suggested that the incidence of left ventricular diastolic dysfunction (LVDD) in BD is related to the geographic distribution of patients. 12 In a previous study, the occurrence of intracardiac thrombi, aortic valve regurgitation, and pericardial effusion in Egyptian patients with BD were documented.…”
mentioning
confidence: 99%
“…Measurements were focused on the systolic myocardial wave, the early-diastolic and end-diastolic myocardial waves. Usually, several cardiac cycles were acquired, and the best two consecutive ones were analyzed and averaged [15]. …”
Section: Methodsmentioning
confidence: 99%
“…158 Potential explanations for this dysfunction include the possibility of primary myocardial disease, disturbance of the coronary microcirculation, or the presence of silent ischemia. 157 In one recent study, no differences were found in left ventricular function in systole and diastole at rest and with exercise in patients as compared to healthy control subjects. 159 This discrepancy of the reported studies may be due to the patient selection or to the sensitivity of the assessment methods.…”
Section: Pericarditismentioning
confidence: 96%
“…156 In the first study to use pulsed wave Doppler tissue echocardiography, ventricular diastolic function was found to be abnormal in BD patients as compared to control subjects. 157 Diastolic dysfunction was reported in 37% of patients using transthoracic and multiplane transesophageal echocardiography. 158 Potential explanations for this dysfunction include the possibility of primary myocardial disease, disturbance of the coronary microcirculation, or the presence of silent ischemia.…”
Section: Pericarditismentioning
confidence: 98%